PENGEMBANGAN VIDEO PEMBELAJARAN BERBASIS KINEMASTER PRO V4 PADA MATERI SUHU DAN KALOR DI KELAS XI SMA - Dani Sagita; Azhar Azhar; Dina Syaflita (STKIP Pesisir Selatan, 2022)
The purpose of this study was to develop learning media in the form of learning videos based on the Kinemaster Pro V4 application on temperature and heat material in class XI SMA. The development of learning videos was carried out as a solution to the difficulties of learning physics and the lack of use of learning media to help teachers in the physics learning process. The type of research used is research and development (R&D) using the ADDIE model which consists of five stages, namely the analysis, design, development, implementation, and evaluation stages. The data collection instrument was in the form of a validation sheet given to three validators. The data analysis technique is by calculating the validation assessment score using the average score validity index (r). The results showed that the Kinemaster Pro V4-based learning video on temperature and heat material in class XI SMA that was developed met the valid criteria from the validated aspects including video display (graphical) aspects, program aspects, learning aspects, and curriculum aspects with a validity index of 3 ,70.